2014
DOI: 10.1111/apa.12585
|View full text |Cite
|
Sign up to set email alerts
|

Children born extremely preterm show significant lower cognitive, language and motor function levels compared with children born at term, as measured by the Bayley-III at 2.5 years

Abstract: Extremely preterm children show significant lower cognitive, communicative and motor function levels at 2.5 years compared with children born at term. Bayley-III assessments permit the acquisition of nuanced information about development following extreme prematurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 33 publications
7
54
3
5
Order By: Relevance
“…Similar to findings in the EXPRESS study (22), the BSID III language and motor subscales in this study differed in mean and SDs as compared to BSID III reference data ( Table 1). Therefore, we used the results of each subscale in the analysis instead of language and motor indexes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to findings in the EXPRESS study (22), the BSID III language and motor subscales in this study differed in mean and SDs as compared to BSID III reference data ( Table 1). Therefore, we used the results of each subscale in the analysis instead of language and motor indexes.…”
Section: Discussionsupporting
confidence: 84%
“…Another possibility is that the BSID III gross motor subscale relies less on visual tracking abilities since no moving objects are included among the tasks at this age level. In the Swedish EXPRESS study, a national population-based study of infants born before 27 gestational weeks, the gross motor subscale identified fewer children with disability at 2.5 y corrected age (prevalence 7%) than the other BSID III subscales (prevalence 11-15%) (22).…”
Section: Neonatal Risk Factorsmentioning
confidence: 99%
“…Even at term-corrected age, the brains in preterm infants may show compromised gray matter volume and altered developmental trajectory (1), probably explaining delayed neonatal arousal (2,3) and immature neuromuscular function and brain electroencephalography (4). In more longterm studies, preterm infants have shown reduced postural complexity (5) and lowered motor function (6), potentially persisting until school age (7), or even into adulthood (8). Thus, early impairment of physical locomotion in preterm infants may have long-term consequences.…”
mentioning
confidence: 99%
“…Egy 2014-es vizsgálatban 2,5 éves korú extrém mérté-kű koraszülött gyermekek pszichomotoros teljesítmé-nyét kilenc hónapra született gyermekekkel összehason-lítva azt tapasztalták, hogy mind kognitív, nyelvi és motoros szinten is szignifikánsan alacsonyabb mutatókkal jellemezhetők a koraszülött gyermekek [24]. Sansavini és mtsai [25] szintén hasonló eredményeket tapasztaltak.…”
Section: A Koraszülött Gyermekek Fejlődési Jellegzetességeiunclassified